The Moroccan Meska Horra: A Natural Candidate for Food and Therapeutic Applications - Abdessamad Beraich; Burak Dikici; Hammadi El Farissi; Daniela Batovska; Krastena Nikolova; Yousra Belbachir; Anass Choukoud; Nour Eddine Bentouhami; Abdeslam Asehraou; Abdelmoneam Talhaoui (Foods)
Mastic gum (Pistacia lentiscus L. resin), traditionally known as Meska Horra in Morocco, is valued for its bioactive properties, although its composition varies depending on its geographical origin. The essential oil profile is also influenced by the extraction method used. This study evaluates the chemical composition, bioactivity, and extraction efficiency of Meska Horra essential oil from eastern Morocco. Specifically, it explores its potential as a natural preservative and functional food ingredient by comparing various extraction methods and their impact on the profiles of volatile compounds. The essential oil obtained through hydrodistillation yielded 1.4% and met the standards of the European Pharmacopoeia despite differing in composition and quantity from Chios mastic gum. The major constituents were α-pinene, β-pinene, and D-limonene, comprising 55% of the oil. The oil demonstrated significant antioxidant and antimicrobial activity, supporting its potential application in food preservation. Molecular docking indicated that caryophyllene and its oxide are key bioactive compounds, although their effectiveness may be enhanced by synergistic interactions. Comparative analysis of extraction methods showed that headspace (HS) extraction captured highly volatile monoterpenes, while solid-phase microextraction (SPME) and ultrasound-assisted SPME (US-SPME) were more effective at extracting compounds such as cis-ocimene and limonene. US-SPME also extracted higher levels of m-cymene but lower levels of α-pinene. These findings highlights the importance of optimizing extraction methods and further investigating the role of synergistic effects in foods and pharmaceutical applications.